Pengembangan LKPD Berbasis Project Based Learning Membuat Desain Kemasan Pada Mata Pelajaran Produk Kreatif Kewirausahaan Kelas XI Tata Busana Di SMKN 3 Jember - Frinoka Meidila; Mein Kharnolis (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research aims to develop project-based learning LKPD teaching materials on packaging design. This research method is the development of the ADDIE model with three stages, namely analysis, design, development. The instrument used is a validation sheet by material experts and media experts. The data obtained was then calculated using the percentage formula which was then described in descriptive sentences. The results showed that the project-based learning LKPD based on packaging design material that had been validated by the material got a percentage value of 84% which was in the feasible category. While the results of validation by media experts received a percentage value of 81% which is in the feasible category. The conclusion of this study is that the feasibility results of developing project-based learning-based LKPD on packaging design material are in the feasible category.